Digital Transformation and Performance Optimization at XYZ Higher Education through TOGAF-Based Enterprise Architecture - Febriyani, Widia; Samsudin, Samsudin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Information technology (IT) has become an indispensable component of the corporate landscape in the digital age, reshaping how organizations operate. The rapid development of IT has revolutionized traditional business methods, transforming them into more efficient, technology-driven operations. Companies and institutions worldwide increasingly focus on digitalization to integrate business processes, streamline workflows, and enhance productivity. XYZ University in Indonesia, as an educational institution, is not immune to this shift. To stay competitive and efficient, the university aims to implement fundamental principles of coordination and integration within its internal structure and with external partners. A central goal of XYZ University’s digital transformation efforts is to streamline its business processes and bolster its cybersecurity framework. These initiatives are critical to the university’s broader strategy of developing a robust Enterprise Architecture (EA). This research focuses on the Academic Directorate and addresses three fundamental domains: business processes, data and information management, and application systems. By concentrating on these areas, the research aims to develop an EA blueprint to provide a comprehensive framework for enhancing the university’s digital capabilities. This blueprint is intended to serve as a strategic solution for integrating information systems, ensuring smooth data flow across departments, and improving the overall efficiency of business processes within the institution. It will help XYZ University achieve its digital transformation goals in the long term, leading to better coordination, more robust security, and higher operational efficiency.